Structural characterization of the Zalm district, West Saudi Arabia, using aeromagnetic data: An approach for gold mineral exploration - Alzahrani Hassan; Ibrahim Elkhedr (Open Geosciences)
The Zalm district in western Saudi Arabia has drawn significant attention from those interested in exploring for gold mineralization. In the present study, the structural framework and major structural trends that most likely control the distribution of the gold mineral deposits in the Zalm district are interpreted using aeromagnetic data. For this purpose, the aeromagnetic data were subjected to enhancement filters to make the structural interpretation of the data easier. In this respect, the data were reduced to the north magnetic pole and processed through two enhancement filters: the analytical signal (AS) and the first vertical derivative (1VD). Lineament analysis of aeromagnetic maps suggests that three major fault sets dissected the Zalm district trending in the northwest (NW), northeast (NE), and north-south (NS) directions. These faults likely affected the mineralization occurrences in the Zalm district and could serve as important structural conduits for hydrothermal fluid channeling. Based on the current results, four localities were identified as promising for additional mineral resource investigation. These localities are delimited and dissected by the NW, NE, and NS faulting and are intruded by a series of felsic and mafic–ultramafic intrusions. It is likely that, in similar to Bi'r Tawilah where the location is structurally controlled by NW and NS faulting, the interpreted felsic and mafic served as sources of mineralizing fluids which remobilized the ore in the district by channeling through the faults. Three of the suggested localities, one lying in close proximity to Zalm city and two along the Rada and Nabitah fault zones, are characterized by high magnetic anomalies, indicating the presence of ultramafic and volcanic rocks that most likely host mineralization. The fourth locality situated in the central part of the district is marked by an elongated N–S low magnetic anomaly, interpreted as felsic diorite and granite rocks delimited by N–S faulting. To accurately detect mineral resources in the selected zones, additional comprehensive and in-depth geological and geophysical research are recommended.